A Picky Predator and Its Prey: How Snow Conditions and Ptarmigan Abundance Impact Gyrfalcon Feeding Behaviour and Breeding Success - Annabel Josien Slettenhaar; Jan Eivind Østnes; Børje Cato Moen; Rolf Terje Kroglund; Torgeir Nygård; Erlend Birkeland Nilsen (Ecology and Evolution)
ABSTRACT Species interactions can be altered by climate change but can also mediate its effects. The gyrfalcon (Falco rusticolus) and the ptarmigan (Lagopus spp.) form a predator–prey couple that reflects the dynamics of boreal, tundra, and alpine ecosystems. To determine how climate change may impact the alpine food web, we investigated how ptarmigan abundance and local weather impact gyrfalcon diet and feeding behaviour, nest occupancy, and reproductive success. Using wildlife cameras, we monitored gyrfalcon nests throughout the nestling period to collect data on diet and feeding behaviour. We quantified the gyrfalcon's functional response by describing how ptarmigan kill rates relate to ptarmigan density. Additionally, we quantified the gyrfalcon's numerical demographic and aggregative response by describing how gyrfalcon reproductive success and nest occupancy, respectively, were related to ptarmigan density, using data from large‐scale monitoring projects. Ptarmigan were the dominant prey species, representing 98% of the diet. The proportion of ptarmigan in the gyrfalcon diet and gyrfalcon breeding success increased in springs with more snow, but breeding success decreased with more snow during the nestling period. Gyrfalcon reproductive success was positively related to ptarmigan density, but gyrfalcon nest occupancy and the ptarmigan kill rate were not related to ptarmigan density. These results indicate that the effect of climate change is not straightforward, and investigating how (a)biotic factors impact both prey and predator is relevant in predicting how a predator will respond to climate change. Following current climate predictions, spring will occur earlier, which will change the food‐web structure through prey availability and diversity and through interactions with other species. This requires adaptations from gyrfalcons and other predators. We emphasise that the impact of climate change on predators and other species can be more accurately evaluated on a multi‐species level rather than individually.